Phytochemical and protein extraction of Golden shower tree (Cassia fistula) - Monkolval, Patcharee; Insuwan, Wilaiporn; Nanuam, Jakkaphun; Bunjan, Kamolrat; Phosai, Weerayut; Thanomsit, Chutima; Wattanakornsiri, Amnuay; Phimchan, Paongpetch (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 1 (2021): January - March 2021, 2020)
The objective of study was to perform a crude extract from leaves and flowers of Cassia fistula by using two types of solvents; ethanol and hexane in order to reduce chemicals or antibiotics application. After studying phytochemical substances by testing color development and sedimentation in both fresh and dry forms, we found that fresh leaves had higher phytochemical properties than flowers. There were 8 important properties found; alkaloids, flavonoids, coumarin, tannins, flobatannins. terpenoids, steroids, and cardiac glycosides. Fresh leaves were used in protein form identification by using SDS-PAGE technique, the important protein found having molecular weight  between 23 to 80 kDa consisting of seven bands; 80, 71, 52, 48, 40, 35, and 23 kDa, respectively. Moreover, their antibacterial activity was studied by using disc diffusion method and dilution method and found that the crude extract had inhibitory activity on Gram positive bacteria, Staphylococus aureus, and gram negative bacteria, Pseudomonas aeruginosa, compared with the antibiotic, chloramphenicol. The crude extract from fresh leaves showed inhibitory activity in Staphylococus aureus higher than from dried leaf extract. In the concentration of 3 mg / ml, the largest inhibitor zone observed was 12.67 ± 3.33 mm. For gram negative bacteria, the largest inhibitory zone found in the treatment of dried leaf extract with the concentration of 3 mg / ml was 12.33 ± 3.88 mm. In the study of antibacterial activity by dilution method, it was found that the extracts in all concentration could inhibit Staphylococus aureus and Pseudomonas aeruginosa . Based on these results, we can conclude that Cassia fistula leaves can be used to perform crude extracts and then applied for bacterial inhibition.